Effects of cooling rates during depuration on the quality of Pacific oysters (Crassostrea gigas) at anhydrous preservation stage - Shijie Bi; Changhu Xue; Yunqi Wen; Xin Du; Qianqian Xue; Zhaojie Li; Hongying Liu (Food Chemistry: X, 2023)
The Pacific oyster could be affected by several pressure sources during cold chain logistics, which reduce the quality of oyster, and even improve its mortality. For improving the quality of oyster, the effects of depuration process at different cooling rates (1, 3, 7, 11 and 16 °C/h) on selected Pacific oyster were studied. The results indicated that extreme fluctuations in the depuration temperatures could affect the survival rates and qualities of oysters. The oysters exhibited low survival rates, glycogen contents and pH values at an increased cooling rate. Their contents in the 1 °C/h group after 3 d preservation were 100 %, 16.30 ± 1.64 mg/100 g and 6.72 ± 0.01, respectively, while there were 71 %, 7.72 ± 0.88 mg/100 g and 6.53 ± 0.01 in the 16 °C/h group after 3 d preservation, respectively. Furthermore, the ATP-related compounds were affected by the different cooling rates. AMP and IMP were the main ATP-related compounds, and their contents in the 1 °C/h group after 3 d preservation were 37.21 ± 1.10 mg/100 g and 29.47 ± 1.10 mg/100 g, respectively, while there were 32.07 ± 1.10 mg/100 g and 13.16 ± 1.60 mg/100 g in the 16 °C/h group after 3 d preservation, respectively. The proportions of the total umami, as well as the sweet amino acids also decreased, the proportions of the umami amino acids and sweet amino acids in the total amino acids, were 31.37%–38.80%, and their proportions in 1 °C/h group were higher than that in 16 °C/h group. Conversely, the fatty acid content of each group exhibited significant differences. Combined with the above results, the oyster maintained a high survival rate and higher quality at a cooling rate of 1 °C/h during depuration.